Malay Culture-Based Psychoeducation: Strategies for Improving Students' Self-Regulated Learning (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
Self-Regulated Learning is an essential skill that students must possess to be able to learn independently, intentionally, and sustainability. In fact, the are some of students find it hard to manage motivation, concentration, and their dicipline. This article examines the application of psychoeducation based on Malay local wisdom as an innovative strategy to improve students' self-regulated learning.The local wisdom raised is based on moral and educational values ​​in Raja Ali Haji's Gurindam Dua Belas, which are relevant to aspects of self-control, discipline, responsibility, and emotional regulation. The method used is a literature review by examining various studies related to psychoeducation, self-regulated learning, and cultural integration in counseling interventions. The results of the study indicate that Malay culture-based psychoeducation has the potential to improve self-regulated learning through three main aspects, namely (1) strengthening intrinsic motivation, (2) developing self-awareness and emotional regulation, and (3) internalizing cultural values ​​as guidelines in managing the learning process. These findings highlight the importance of developing higher education interventions that are contextual, integrated, and culturally grounded